The complete mitochondrial genome of Turbo cornutus (Trochida: Turbinidae) and its phylogeny analysis - Eiseul Kim; Jinhyuk Kim; Yumin Lee; Gyoungju Nah; Hae-Yeong Kim (Mitochondrial DNA. Part B. Resources, 2022)
The complete mitochondrial genome sequence of Turbo cornutus, a species of the Turbinidae family, was characterized from the de novo assembly of Illumina paired-end sequencing data. The complete mitochondrial genome of T. cornutus was 17,297 bp in length and comprised of 13 protein-coding genes, 25 tRNAs, and two rRNAs. The base composition of T. cornutus exhibited a high A + T content of 71.17%. The phylogenetic analysis of T. cornutus with 14 species from GenBank revealed that the ancestor of Astralium haematragum and Bolma rugosa was diverged from T. cornutus.